Služba sociální prevence raná péče v kontextu evaluace individuálních potřeb klientů - Šándorová, Zdenka (Univerzita Pardubice, 2010)
The author of the article informs about historical connections and the current situation of social prevention – early care services in the Czech Republic. Based on individual needs of clients she also evaluates the quality of services in a particular institution – the Centre for Early Care in Pardubice.
Keywords: early care; centre for early care in Pardubice; evaluation; individual needs of clients